Beyond the Binary: Exploring the Lived Experiences of Gender Dysphoric Adolescents in Indonesia - Andi Fatihah Syahrir; Ni Made Nova Indriyani; Rheina Weisch Fedre; Shina Abdulkadir (Scientia Psychiatrica, 2024)
Introduction: Gender dysphoria among adolescents is increasingly recognized globally, yet research on the lived experiences of transgender youth in Indonesia remains limited. This study aimed to explore the unique challenges, coping mechanisms, and support needs of Indonesian adolescents navigating gender dysphoria within a sociocultural context characterized by traditional gender norms and limited access to specialized healthcare. Methods: In-depth, semi-structured interviews were conducted with 15 adolescents (aged 13-19) who identified as experiencing gender dysphoria. Participants were recruited through LGBTQ+ youth organizations and community centers in Jakarta and Surabaya. Data were analyzed using thematic analysis to identify key themes and patterns within their narratives. Results: Four major themes emerged: (1) Early Recognition and Internal Conflict: Participants described an early awareness of their gender identity incongruence, often accompanied by feelings of confusion, shame, and fear due to societal expectations and potential rejection. (2) Navigating Disclosure and Social Support: Coming out to family and peers was a significant challenge, with varied responses ranging from acceptance to rejection. Support networks, primarily found within online communities and LGBTQ+ organizations, played a crucial role in fostering resilience. (3) Barriers to Accessing Healthcare: Participants reported significant obstacles in accessing gender-affirming care, including limited availability of specialized healthcare providers, financial constraints, and lack of family support. (4) Resilience and Hope for the Future: Despite the challenges, participants expressed resilience, hope, and a strong desire to live authentically. They emphasized the importance of self-acceptance, peer support, and advocacy for greater understanding and acceptance of gender diversity in Indonesia. Conclusion: This study provides valuable insights into the experiences of gender dysphoric adolescents in Indonesia. Findings highlight the urgent need for increased awareness, improved access to gender-affirming care, and supportive interventions to promote the well-being of this vulnerable population.